(untitled) (Research, Society and Development, 2021)
The classroom is constituted by diversity, in it we come across students from different social classes and different special educational needs, among which is the Autistic Spectrum Disorder (ASD). Contact with this segment of students has demanded from education professionals, especially art teachers, the need to improve their educational and pedagogical practices in order to understand the specificities that each student has in the teaching/learning process. The aim of this study is to analyze how art teaching influences the socialization and learning process of autistic students. To achieve the objective, the methodology used is characterized as being a literature review, for this the study was divided into three parts: firstly, there is a mention of the characteristics and diagnoses of the Autistic Spectrum Disorder, in the second moment, we will continue with a survey of the laws that regulate inclusive education in the country, finally, we will investigate whether art in the areas of music, theater and dance contribute to the development of individuals with ASD. It found that autism is characterized by the lack of interest in maintaining interpersonal relationships, difficulties in language and communication and peculiar interests in certain objects and stereotyped behaviors, in this sense concluded that recreational activities involving dance, music and theater provide a considerable improvement in the cognitive, psychomotor aspect as well as in the emotional aspect and in affective relationships.